DO FIRMS SEEK A TARGET BOARD STRUCTURE? EVIDENCE FROM THE POST‐SOX PERIOD. (1st July 2019) - Chung, Chune Young; Liu, Chang; Paul, Donna L.
Abstract: We investigate whether firms restructure board composition to align with changes in their contracting environment. Board size and independence increase with firm complexity, consistent with theoretical predictions. However, the hypothesized negative relation between board independence and information costs is evident only for firms completing acquisitions. Furthermore, board independence increases to offset increases in CEO power in a sample of firms making acquisitions, but decreases when CEO power increases in a large cross‐section of firms. We conclude that after the Sarbanes–Oxley Act of 2002, firms face constraints adjusting to target board structure, but these constraints can be mitigated by a shock to the contracting environment via acquisition.